Recently Intensified Tropical‐Extratropical Linkage Modulated by Arctic Sea Ice Loss - Xiang Zhang; Bingyi Wu (Geophysical Research Letters)
Abstract Through data analysis and numerical simulations, this study reveals the winter Arctic Warming Pattern (AWP), characterized by anticyclonic anomalies over the North Pacific and the Urals, which plays a pivotal role in linking the Arctic and tropics. The AWP is significantly correlated with the tropical Pacific Walker Circulation (PWC). Since the decadal shift of the AWP in 2003, the relationship between the AWP and the PWC has intensified over the past two decades. Model simulations suggest that this enhanced AWP‐PWC linkage is attributed to the recent shift to a low Arctic sea ice state after 2004. The results show that the shrinking Arctic sea ice promotes the AWP, contributing to the robust responses of zonal winds over the Pacific, further enhancing the PWC and ultimately driving the recent intensification of the tropical‐extratropical linkage.